Radiative mechanism and surface modification of four visible deep level defect states in ZnO nanorods. Issue 2 (14th December 2015) - Barbagiovanni, E. G.; Reitano, R.; Franzò, G.; Strano, V.; Terrasi, A.; Mirabella, S.
Abstract : We controlled the visible emission from deep level defect states in ZnO nanorods by annealing; identified blue, green, orange, and red emitting defects; and discussed the role of Zni on visible emission. Abstract : Visible luminescence from ZnO nanorods (NRs) is attracting large scientific interest for light emission and sensing applications. We study visible luminescent defects in ZnO NRs as a function of post growth thermal treatments, and find four distinct visible deep level defect states (VDLSs): blue (2.52 eV), green (2.23 eV), orange (2.03 eV), and red (1.92 eV). Photoluminescence (PL) studies reveal a distinct modification in the UV (3.25 eV) emission intensity and a shift in the visible spectra after annealing. Annealing at 600 °C in Ar (Ar600) and O2 (O600) causes a blue and red-shift in the visible emission band, respectively. All samples demonstrate orange emission from the core of the NR, with an additional surface related green, blue, and red emission in the As-Prep, Ar600, and O600 samples, respectively. From PL excitation (PLE) measurements we determine the onset energy for population of the various VDLSs, and relate it to the presence of an Urbach tail below the conduction band due to a presence of ionized Zni or Zni complexes. We measured an onset energy of 3.25 eV for the as prepared sample. The onset energy red-shifts in the annealed samples by about 0.05 to 0.1 eV indicating a change in the defect structure, which we relate to the shift in the visible emission. We then used X-ray photoemission spectroscopy (XPS), and elastic recoil detection analysis (ERDA) to understand changes in the surface structure, and H content, respectively. The results of the XPS and ERDA analysis explain how the chemical states are modified due to annealing. We summarize our results by correlating our VDLSs with specific intrinsic defect states to build a model for PL emission in ZnO NRs. These results are important for understanding how to control defect related visible emission for sensing and electroluminescence applications.